Ghoulfriends 'til the end / 4., Ghoulfriends. - Daneshvari, Gitty (Daneshvari, Gitty. Monster High (New York : 2012- ), 2014)
It is bad times at Monster High because a secret organization of older monsters is determined to preserve their hierarchy, and it is up to the ghoulfriends--Rochelle, Rebecca, and Venus--to stop ASOME, protect their school, and rescue their friends.